El cálculo racional para elegir o la deliberación con sabiduría (2016)
ABSTRACT: This article questions the normative character of measurement for decision-making and it proposed to choose wisely as a more suitable alternative to decide in uncertainty. Science of measurement, in principle, supposed to raise an explanatory theory about how agents decide, however, at the same time it indicates a seemingly reasonable strategy to choose. A reduction of uncertainty is proposed in explanatory proposal that emerges in modernity with a normative consideration of rationality; contrary to a discussion with wisdom whose starting point is a turn on itself. The text has four sections. The first section discusses the epistemological criteria underlying the science of measurement to decide, also presents the Theory of Expected Utility incorporating the criteria. The second shows the process using a rational agent to decide in uncertainty. The third section makes a comparison between the normative character of a science of measurement and deliberation with wisdom. Finally, the fourth shows a distinction between epistemic uncertainty and ontological uncertainty.